A preparation method of magnetic biochar adsorbent for valuable metal recovery of lithium batteries

By loading Fe3O4 on biochar material, magnetic biochar adsorbent is formed, which solves the problem of low recycling efficiency of valuable metals in waste lithium-ion batteries, and achieves efficient and low-cost recycling and separation of valuable metals, which is environmentally friendly Features.

CN115920849BActive Publication Date: 2024-12-13XIAN JINZANG MEMBRANE ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202310125105.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-16
Publication Date
2024-12-13
Estimated Expiration
2043-02-16

AI Technical Summary

Technical Problem

The prior art has low recycling efficiency of valuable metals such as cobalt and nickel in waste lithium-ion batteries, and traditional methods have problems with high economic costs, environmental pollution and complex process.

Method used

Using magnetic biochar adsorbent, Fe3O4 is loaded on biochar material, and its rich pore structure and high specific surface area are used, combined with magnetic properties, efficient adsorption and separation of valuable metal ions are achieved.

Benefits of technology

It realizes efficient recycling of valuable metal ions such as cobalt and nickel in waste lithium batteries, reduces economic costs, and is simple to separate and reuse through external magnetic fields, which has the advantages of environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115920849B_ABST
    Figure CN115920849B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of recycling valuable metals in waste lithium batteries, and in particular to a method for preparing a magnetic biochar adsorbent for recycling valuable metals in lithium batteries. The preparation method uses biochar as a carrier, loads Fe3O4 on the original biochar material, and magnetizes it to finally form a porous carbon material adsorbent. The magnetic biochar adsorbent for recycling valuable metals in lithium batteries prepared by the present invention has a rich pore structure and a high specific surface area, is simple to synthesize, has low raw material cost, and has the advantages of being environmentally friendly. It has good adsorption performance for valuable metal ions in waste batteries, and magnetization also allows the adsorbent to be better separated from the solution, which is beneficial to the subsequent desorption and reuse of valuable metal ions, and the magnetic biochar adsorbent can be used multiple times, further reducing economic costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of recycling valuable metals in waste lithium batteries, and in particular to a method for preparing a magnetic biochar adsorbent for recycling valuable metals in lithium batteries. Background Art

[0002] With the rapid development of the new energy vehicle industry, the use of lithium-ion batteries has increased significantly, which has also led to the generation of a large number of waste lithium-ion batteries. The large-scale generation of waste lithium-ion batteries will cause two problems. On the one hand, waste lithium-ion batteries contain toxic components. On the other hand, waste lithium batteries contain rich valuable metal components such as cobalt, nickel, and manganese. The reasonable recycling of waste lithium-ion batteries can not only achieve the recycling of valuable metals and reduce economic costs, but also play a role in protecting the environment. At present, the recycling of waste lithium-ion batteries mainly focuses on the recycling of lithium ions. There is little research on the recycling of other types of valuable metals such as nickel and cobalt, and it is impossible to efficiently recycle other valuable metal ions.

[0003] At present, the main methods used for the recovery of valuable metals in waste lithium-ion batteries are: solvent extraction, chemical precipitation, ion exchange and electrochemical methods. The solvent extraction method uses a specific organic solvent and metal ion to form a complex, and then selects a suitable reagent to extract the metal. However, the solvent extraction method has high anti-corrosion requirements for equipment, high economic costs, and consumes a large amount of organic reagents during the process. The regeneration cost is high and may cause secondary pollution to the environment. The chemical precipitation method uses the characteristics of metal ions and some specific anions to generate compounds with low solubility. According to the different solubility products of the compounds, the pH value is adjusted to produce precipitates to achieve the separation of valuable metal ions. Although the recovery rate is relatively high, the operation process is relatively cumbersome and complicated, and the pH value is difficult to control during the process. It is not suitable for large-scale production. In addition, the loss of precipitants during the process will cause pollution to the environment. This method has great limitations. The ion exchange method uses a suitable ion exchange resin and uses the different adsorption coefficients of metal ion complexes such as cobalt and nickel to achieve the purpose of separation. Finally, the valuable metal ions are eluted using an eluent. The ion exchange method can recover valuable metal ions with high purity, but it also has great limitations, such as low recovery efficiency and complicated experimental steps in the recovery process, which makes it difficult to meet industrial requirements. The electrochemical method refers to leaching the metal in the electrode material in the form of ions, and then reducing the valuable metal ions through an electrochemical process to obtain valuable metals. The electrochemical method does not require the addition of other solutions or other substances during the process, introduces fewer impurities, and has a higher purity of the recovered product. However, the electrochemical method has high requirements for material pretreatment and consumes more electricity, which has high economic costs. Summary of the invention

[0004] In view of the above problems, the present invention provides a method for preparing a magnetic biochar adsorbent for recovering valuable metals from lithium batteries. The magnetic biochar adsorbent provided by the present invention has a rich pore structure and a high specific surface area, is easy to synthesize, has low raw material cost, and is environmentally friendly. It has good adsorption performance for valuable metal ions in waste batteries, and magnetization also allows the adsorbent to be better separated from the solution, which is beneficial to the subsequent desorption and reuse of the valuable metal ions. The magnetic biochar adsorbent can be used multiple times, further reducing the economic cost of recovering valuable metals in waste lithium batteries.

[0005] The technical solution adopted by the present invention is: a method for preparing a magnetic biochar adsorbent for recovering valuable metals from lithium batteries, the specific steps are:

[0006] S1: Select wood as biomass raw material, wash and remove impurities on the wood surface and air-dry it, then crush it, sieve 40-60 mesh particles for later use, and dry the particles for later use;

[0007] S2: pyrolyzing the reserved particles at a temperature range of 600-800° C., and cooling to room temperature after the pyrolysis treatment;

[0008] S3: The cooled spare particles are crushed again, sieved through 80-100 mesh particles, and soaked in a HCl solution with a molar concentration of 0.5-3 mol / L for 4-6 hours. After soaking, the filtered product is filtered, and the filtered product is repeatedly rinsed with deionized water until it is neutral. The rinsed product is dried, and the biochar material is obtained after drying;

[0009] S4: Deionized water and the biochar material prepared in step S3 are weighed and mixed respectively, the mass ratio of deionized water to biochar material is 8:1-12:1, and a magnetic stirrer is used to stir evenly to form a mixed material; FeCl3·6H2O, FeSO4·7H2O and deionized water with a molar ratio of 1.2:1-1.8:1 are mixed evenly to form a mixed solution, the molar concentration of Fe element in the mixed solution is 0.2-0.3 mol / L, the mixed material with a volume ratio of 0.3:1-0.6:1 is taken and mixed with the mixed solution, and stirred at a speed of 120-180 r / min for 30-60 min, and the pH value of the solution is adjusted to the range of 10.0-11.0 to promote precipitation, and then the stirring is continued, and the solution is heated to a slight boiling state, and the slight boiling state lasts for 40-60 min, and the stirrer is turned off, and the solution is filtered after cooling to obtain a precipitated solid;

[0010] S5: The precipitated solid obtained after filtration is repeatedly washed with deionized water until its pH value is neutral, and then the solid is washed with anhydrous ethanol. The washed solid is dried to obtain a magnetic biochar adsorption material, and the magnetic biochar adsorption material is ground using a ball mill to obtain a magnetic biochar adsorbent for valuable metal recovery of lithium batteries.

[0011] The wood selected in step S1 is one or more of paulownia, pine, willow, apple and peach.

[0012] In step S1, an oven is used for drying, the temperature range of the oven is 60 to 80° C., and the drying time is 18 to 24 hours.

[0013] In step S3, an oven is used for drying, the temperature range of the oven is 60-80° C., and the drying time is 6-8 hours.

[0014] In the step S4, the pH value of the solution is adjusted to a range of 10.0 to 11.0, and the pH value of the solution is adjusted by dropwise adding NH3·H2O into the solution.

[0015] In step S5, an oven is used for drying, the temperature range of the oven is 60-80° C., and the drying time is 8-10 hours.

[0016] In the step S5, the magnetic biochar adsorption material is ground using a ball mill, the grinding time is 0.5h to 2h, and the particle size of the magnetic biochar adsorption material after grinding is 6.0 to 8.0 μm.

[0017] A method for preparing a magnetic biochar adsorbent for recovering valuable metals from lithium batteries, wherein the magnetic biochar adsorbent has a specific surface area of ​​300 to 500 m 2 / g, in the waste lithium battery leachate recovery test, Co 2+ Recovery rate ≥ 89%, Ni 2+ Recovery rate ≥90%, Mn 2+ Recovery rate ≥88%.

[0018] The micro-boiling state of the present invention means that small bubbles appear on the surface of the liquid in the container, and the liquid at the heating point boils, but the liquid in the container as a whole does not boil, and is in a state before boiling.

[0019] The beneficial effects of the present invention are: 1. The preparation method of the present invention loads Fe3O4 on the biochar material, and the biochar material has a porous structure. After loading Fe3O4, the adsorption performance of the biochar adsorbent is improved, and it has a higher recovery efficiency for valuable metal ions; 2. The magnetic biochar adsorbent for valuable metal recovery of lithium batteries prepared by the present invention has a rich pore structure and a higher specific surface area, is simple to synthesize, has low raw material cost, and has the advantages of being environmentally friendly, and the preparation process is green and pollution-free; 3. After the magnetic biochar adsorbent for valuable metal recovery of lithium batteries prepared by the present invention adsorbs valuable metal ions, it can be quickly separated by an external magnetic field, which is beneficial to the subsequent desorption and reuse of the valuable metal ions, and the magnetic biochar adsorbent can be used multiple times, which is simple to recover and has a lower cost than existing adsorbents.

[0020] The following is a further description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a flow chart for preparing a magnetic biochar adsorbent for valuable metal recovery in lithium batteries according to an embodiment of the present invention.

[0022] Figure 2 This is a scanning electron microscope image of a magnetic biochar adsorbent for recovering valuable metals from lithium batteries according to an embodiment of the present invention. DETAILED DESCRIPTION

[0023] Example 1

[0024] like Figure 1 As shown, a method for preparing a magnetic biochar adsorbent for recovering valuable metals from lithium batteries comprises the following specific steps:

[0025] S1: Select wood as biomass raw material, wash and remove impurities on the wood surface and air-dry it, then crush it, sieve 40-60 mesh particles for later use, and dry the particles for later use;

[0026] S2: pyrolyzing the reserved particles at a temperature range of 600-800° C., and cooling to room temperature after the pyrolysis treatment;

[0027] S3: The cooled spare particles are crushed again, sieved through 80-100 mesh particles, and soaked in a HCl solution with a molar concentration of 0.5-3 mol / L for 4-6 hours. After soaking, the filtered product is filtered, and the filtered product is repeatedly rinsed with deionized water until it is neutral. The rinsed product is dried, and the biochar material is obtained after drying;

[0028] S4: Weigh deionized water and the biochar material prepared in step S3 respectively and mix them, the mass ratio of deionized water to biochar material is 8:1-12:1, and use a magnetic stirrer to stir evenly to form a mixed material; prepare an iron salt solution, mix FeCl3·6H2O, FeSO4·7H2O and deionized water in a molar ratio of 1.2:1-1.8:1 to form a mixed solution, the molar concentration of Fe element in the mixed solution is 0.2-0.3 mol / L, take the mixed material with a volume ratio of 0.3:1-0.6:1 and mix the mixed solution, stir at a speed of 120-180 r / min for 30-60 min, adjust the pH value of the solution to the range of 10.0-11.0 to promote precipitation, and then continue to stir and heat to a slight boiling state, the slight boiling state lasts for 40-60 min, turn off the stirrer, filter the solution after cooling, and obtain a precipitated solid;

[0029] S5: The precipitated solid obtained after filtration is repeatedly washed with deionized water until its pH value is neutral, and then the solid is washed with anhydrous ethanol. The washed solid is dried to obtain a magnetic biochar adsorption material, and the magnetic biochar adsorption material is ground using a ball mill to obtain a magnetic biochar adsorbent for valuable metal recovery of lithium batteries.

[0030] Biochar material is a type of porous granular carbon material formed by pyrolysis of natural biomass under anaerobic or oxygen-free conditions. Biochar material is a porous material with stable properties, so it is widely used in chemical industry, environmental protection and other fields. Biochar has the characteristics of easy availability of raw materials, low cost, large specific surface area, etc. It has great potential for application in the field of environmental protection and governance. Its biochar material has also achieved good results as an adsorbent. Magnetic biochar adsorbents have high adsorption properties for valuable metals, and after adsorption, they can be recovered through an external magnetic field. The operation is simple, the cost is low, and it is environmentally friendly. Figure 2 As shown, the preparation method of the present invention loads Fe3O4 on the biochar material, and the biochar material has a porous structure. After loading Fe3O4, the adsorption performance of the biochar adsorbent is improved, and it has a higher recovery efficiency for valuable metal ions; the magnetic biochar adsorbent for valuable metal recovery of lithium batteries prepared by the present invention can be quickly separated by an external magnetic field after adsorbing valuable metal ions. Compared with existing adsorbents, the recovery is simple and the cost is low.

[0031] The wood selected in step S1 is one or more of paulownia, pine, willow, apple and peach.

[0032] In step S1, an oven is used for drying, the temperature range of the oven is 60 to 80° C., and the drying time is 18 to 24 hours.

[0033] In step S3, an oven is used for drying, the temperature range of the oven is 60-80° C., and the drying time is 6-8 hours.

[0034] In the step S4, the pH value of the solution is adjusted to a range of 10.0 to 11.0, and the pH value of the solution is adjusted by dropwise adding NH3·H2O into the solution.

[0035] In step S5, an oven is used for drying, the temperature range of the oven is 60-80° C., and the drying time is 8-10 hours.

[0036] In the step S5, the magnetic biochar adsorption material is ground using a ball mill, the grinding time is 0.5h to 2h, and the particle size of the magnetic biochar adsorption material after grinding is 6.0 to 8.0 μm.

[0037] A method for preparing a magnetic biochar adsorbent for recovering valuable metals from lithium batteries, wherein the magnetic biochar adsorbent has a specific surface area of ​​300 to 500 m 2 / g, in the waste lithium battery leachate recovery test, Co 2+ Recovery rate ≥ 89%, Ni 2+ Recovery rate ≥90%, Mn 2+ Recovery rate ≥88%.

[0038] Example 2

[0039] This embodiment adopts the preparation method of a magnetic biochar adsorbent for valuable metal recovery of lithium batteries described in Example 1, and the specific process is as follows:

[0040] S1: clean and air-dry the poplar branches, grind the cleaned and air-dried poplar branches with a plant grinder, and keep the part that passes through a 40-mesh sieve for later use; set the oven at 70° C. to dry the sieved poplar branches for 20 hours;

[0041] S2: Put the sieved poplar branches into a crucible, put it into a muffle furnace, set the temperature to 600 °C, treat for 6 hours, and then cool to room temperature;

[0042] S3: Grind the cooled sample with a plant crusher and pass it through an 80-mesh sieve; treat the sample with 1 mol / L HCl for 5 hours; filter the sample with a suction filtration device and repeatedly rinse the filtered product with deionized water until it is neutral; dry the product obtained in the previous step in an oven set at 70°C for 6 hours; obtain the poplar branch biochar material after drying and place it in a sample bag;

[0043] S4: Weigh 10g of poplar branch biochar material and mix it with 100ml of deionized water in a beaker to obtain solution 1; dissolve 10g of FeCl3·6H2O and 5.7g of FeSO4·7H2O in 200mL of deionized water to obtain solution 2; mix the above two solutions and stir them at a speed of 180r / min for 30min using a magnetic stirrer; add NH3·H2O dropwise to the mixed solution until the pH value of the solution is adjusted to 10.0, and stir for 2h; turn on the heating switch, heat to 95℃, and continue stirring for 1h; wait for it to cool, and filter the solution using a suction filtration device;

[0044] S5: The filtered product is repeatedly washed with deionized water until it is neutral; the product washed with deionized water is washed with anhydrous ethanol; the washed solid is placed in an oven at 70°C and dried for 8 hours; it is ground with a ball mill to obtain a magnetic biochar adsorbent.

[0045] Example 3

[0046] This embodiment adopts the preparation method of a magnetic biochar adsorbent for valuable metal recovery of lithium batteries described in Example 1, and the specific process is as follows:

[0047] S1: clean and air-dry the poplar branches, grind the cleaned and air-dried poplar branches with a plant grinder, and keep the part that passes through a 40-mesh sieve for later use; set the oven at 70° C. to dry the sieved poplar branches for 20 hours;

[0048] S2: Put the sieved poplar branches into a crucible, put it into a muffle furnace, set the temperature to 600 °C, treat for 6 hours, and then cool to room temperature;

[0049] S3: Grind the cooled sample with a plant crusher and pass it through an 80-mesh sieve; treat the sample with 1 mol / L HCl for 5 hours; filter the sample with a suction filtration device and repeatedly rinse the filtered product with deionized water until it is neutral; dry the product obtained in the previous step in an oven set at 70°C for 6 hours; obtain the poplar branch biochar material after drying and place it in a sample bag;

[0050] S4: Weigh 10g of poplar branch biochar material and mix it with 100ml of deionized water in a beaker to obtain solution 1; dissolve 10g of FeCl3·6H2O and 8.6g of FeSO4·7H2O in 300mL of deionized water to obtain solution 2; mix the above two solutions and stir them at a speed of 180r / min for 30min using a magnetic stirrer; add NH3·H2O dropwise to the mixed solution until the pH value of the solution is adjusted to 10.0, and stir for 2h; turn on the heating switch, heat to 95℃, and continue stirring for 1h; wait for it to cool, and filter the solution using a suction filtration device;

[0051] S5: The filtered product is repeatedly washed with deionized water until it is neutral; the product washed with deionized water is washed with anhydrous ethanol; the washed solid is placed in an oven at 70°C and dried for 8 hours; it is ground with a ball mill to obtain a magnetic biochar adsorbent.

[0052] Example 4

[0053] This embodiment adopts the preparation method of a magnetic biochar adsorbent for valuable metal recovery of lithium batteries described in Example 1, and the specific process is as follows:

[0054] S1: clean and air-dry the poplar branches, grind the cleaned and air-dried poplar branches with a plant grinder, and keep the part that passes through a 40-mesh sieve for later use; set the oven at 70° C. to dry the sieved poplar branches for 20 hours;

[0055] S2: Put the sieved poplar branches into a crucible, put it into a muffle furnace, set the temperature to 600 °C, treat for 6 hours, and then cool to room temperature;

[0056] S3: Grind the cooled sample with a plant crusher and pass it through an 80-mesh sieve; treat the sample with 1 mol / L HCl for 5 hours; filter the sample with a suction filtration device and repeatedly rinse the filtered product with deionized water until it is neutral; dry the product obtained in the previous step in an oven set at 70°C for 6 hours; obtain the poplar branch biochar material after drying and place it in a sample bag;

[0057] S4: Weigh 10g of poplar branch biochar material and mix it with 100ml of deionized water in a beaker to obtain solution 1; dissolve 10g of FeCl3·6H2O and 6.4g of FeSO4·7H2O in 300mL of deionized water to obtain solution 2; mix the above two solutions and stir them at a speed of 180r / min for 30min using a magnetic stirrer; add NH3·H2O to the mixed solution until the pH value of the solution is adjusted to 10.0, and stir for 2h; turn on the heating switch, heat to 95℃, and continue stirring for 1h; wait for it to cool, and filter the solution using a suction filtration device;

[0058] S5: The filtered product is repeatedly washed with deionized water until it is neutral; the product washed with deionized water is washed with anhydrous ethanol; the washed solid is placed in an oven at 70°C and dried for 8 hours; it is ground with a ball mill to obtain a magnetic biochar adsorbent.

[0059] Comparative Example 1: A magnetic biochar adsorbent for recovering valuable metals from lithium batteries was prepared according to the method of Example 2, except that step S4 was not performed in Comparative Example 1.

[0060] Comparative Example 2

[0061] In this comparative example, a magnetic biochar adsorbent for recovering valuable metals from lithium batteries was prepared according to the method of Example 2, except that the molar ratio of FeCl3·6H2O to FeSO4·7H2O was 1.1. The specific process was as follows:

[0062] S1: clean and air-dry the poplar branches, grind the cleaned and air-dried poplar branches with a plant grinder, and keep the part that passes through a 40-mesh sieve for later use; set the oven at 70° C. to dry the sieved poplar branches for 20 hours;

[0063] S2: Put the sieved poplar branches into a crucible, put it into a muffle furnace, set the temperature to 600 °C, treat for 6 hours, and then cool to room temperature;

[0064] S3: Grind the cooled sample with a plant crusher and pass it through an 80-mesh sieve; treat the sample with 1 mol / L HCl for 5 hours; filter the sample with a suction filtration device and repeatedly rinse the filtered product with deionized water until it is neutral; dry the product obtained in the previous step in an oven set at 70°C for 6 hours; obtain the poplar branch biochar material after drying and place it in a sample bag;

[0065] S4: Weigh 10g of poplar branch biochar material and mix it with 100ml of deionized water in a beaker to obtain solution 1; dissolve 10g of FeCl3·6H2O and 9.4g of FeSO4·7H2O in 400mL of deionized water to obtain solution 2; mix the above two solutions and stir them at a speed of 180r / min for 30min using a magnetic stirrer; add NH3·H2O dropwise to the mixed solution until the pH value of the solution is adjusted to 10.0, and stir for 2h; turn on the heating switch, heat to 95℃, and continue stirring for 1h; wait for it to cool, and filter the solution using a suction filtration device;

[0066] S5: The filtered product is repeatedly washed with deionized water until it is neutral; the product washed with deionized water is washed with anhydrous ethanol; the washed solid is placed in an oven at 70°C and dried for 8 hours; it is ground with a ball mill to obtain a magnetic biochar adsorbent.

[0067] Comparative Example 3

[0068] In this comparative example, a magnetic biochar adsorbent for recovering valuable metals from lithium batteries was prepared according to the method of Example 3, except that the molar ratio of FeCl3·6H2O to FeSO4·7H2O was 1.9. The specific process was as follows:

[0069] S1: clean and air-dry the poplar branches, grind the cleaned and air-dried poplar branches with a plant grinder, and keep the part that passes through a 40-mesh sieve for later use; set the oven at 70° C. to dry the sieved poplar branches for 20 hours;

[0070] S2: Put the sieved poplar branches into a crucible, put it into a muffle furnace, set the temperature to 600 °C, treat for 6 hours, and then cool to room temperature;

[0071] S3: Grind the cooled sample with a plant crusher and pass it through an 80-mesh sieve; treat the sample with 1 mol / L HCl for 5 hours; filter the sample with a suction filtration device and repeatedly rinse the filtered product with deionized water until it is neutral; dry the product obtained in the previous step in an oven set at 70°C for 6 hours; obtain the poplar branch biochar material after drying and place it in a sample bag;

[0072] S4: Weigh 10g of poplar branch biochar material and mix it with 100ml of deionized water in a beaker to obtain solution 1; dissolve 10g of FeCl3·6H2O and 5.4g of FeSO4·7H2O in 200mL of deionized water to obtain solution 2; mix the above two solutions and stir them at a speed of 180r / min for 30min using a magnetic stirrer; add NH3·H2O dropwise to the mixed solution until the pH value of the solution is adjusted to 10.0, and stir for 2h; turn on the heating switch, heat to 95℃, and continue stirring for 1h; wait for it to cool, and filter the solution using a suction filtration device;

[0073] S5: The filtered product is repeatedly washed with deionized water until it is neutral; the product washed with deionized water is washed with anhydrous ethanol; the washed solid is placed in an oven at 70°C and dried for 8 hours; it is ground with a ball mill to obtain a magnetic biochar adsorbent.

[0074] The magnetic biochar adsorbents for valuable metal recovery of lithium batteries prepared in Examples 2 to 4 and Comparative Examples 1 to 3 were subjected to waste battery leachate adsorption tests to prepare simulated waste battery leachate, wherein the concentrations of various ions: Co 2+ (20g / L), Ni 2 + (0.55g / L), Mn 2+ (2.2 g / L), take ten beakers, add 500 mL of simulated waste battery leachate respectively, take 3 g of each of the ten adsorbents prepared in Examples 2 to 7 and Comparative Examples 1 to 4, add them into the above ten beakers respectively, and carry out a dynamic adsorption experiment for 12 hours. The experimental results are shown in Table 1.

[0075] Table 1 Dynamic adsorption experimental data of Examples 2 to 4 and Comparative Examples 1 to 3

[0076]

[0077] From the data of Examples 2 to 4 in Table 1, it can be seen that the magnetic biochar adsorbent synthesized by the present invention has good adsorption performance for valuable metal ions in waste batteries. In the test of recycling waste lithium battery leachate, Co2+ Recovery rate ≥ 89.2%, Ni 2+ Recovery rate ≥90%, Mn 2+ The recovery rate is ≥88.3%. Compared with the biochar adsorbent of Comparative Example 1, which has not been magnetized, the magnetic biochar adsorbent synthesized by the present invention not only has improved adsorption performance, but also can be easily and efficiently recovered by means of an external magnetic field, which is of great help for the subsequent reuse of valuable metals. The magnetic biochar adsorbent of the present invention can be well used in the recovery of valuable metal ions in waste batteries. It can be seen from Example 2, Example 3, Comparative Example 2 and Comparative Example 3 that when the molar ratio of FeCl3·6H2O to FeSO4·7H2O is between 1.2 and 1.8, the magnetic biochar adsorbent synthesized by the present invention has a good recovery rate for Co in the waste lithium battery leachate recovery test. 2+ 、Ni 2+ and Mn 2+ Has a higher recovery rate.

[0078] The above examples are merely illustrative of the present invention and do not constitute a limitation on the protection scope of the present invention. All designs identical or similar to the present invention belong to the protection scope of the present invention. The reagents, raw materials or methods described in detail in the present invention are all prior art and will not be further described in the present invention.

Claims

1. A method for recovering valuable metals from lithium batteries using a magnetic biochar adsorbent, characterized in that: The specific surface area of ​​the magnetic biochar adsorbent is 300-500m 2 / g, in the waste lithium battery leachate recovery test, Co 2+ Recovery rate ≥89%, Ni 2+ Recovery rate ≥90%, Mn 2+ Recovery rate ≥88%; The specific steps of the preparation method of the magnetic biochar adsorbent are as follows: S1: Select wood as biomass raw material, wash and remove impurities on the wood surface and air-dry it, then crush it, sieve 40-60 mesh particles for later use, and dry the particles for later use; S2: pyrolyzing the reserved particles at a temperature ranging from 600 to 800°C, and cooling to room temperature after the pyrolysis treatment; S3: The cooled spare particles are crushed again, sieved through 80-100 mesh particles, and soaked in a 0.5-3 mol / L HCl solution for 4-6 hours. After the soaking, the filtered product is repeatedly rinsed with deionized water until it is neutral, and the rinsed product is dried to obtain a biochar material. S4: Deionized water and the biochar material prepared in step S3 are weighed and mixed respectively, the mass ratio of deionized water to biochar material is 8:1-12:1, and a magnetic stirrer is used to stir evenly to form a mixed material; FeCl3·6H2O, FeSO4·7H2O and deionized water with a molar ratio of 1.2:1-1.8:1 are mixed evenly to form a mixed solution, the molar concentration of Fe element in the mixed solution is 0.2-0.3 mol / L, the mixed material with a volume ratio of 0.3:1-0.6:1 is taken and mixed with the mixed solution, and stirred at a speed of 120-180 r / min for 30-60 min, and the pH value of the solution is adjusted to the range of 10.0-11.0 to promote precipitation, and then the stirring is continued, and the solution is heated to a slight boiling state, and the duration of the slight boiling state ranges from 40 to 60 min, and the stirrer is turned off, and the solution is filtered after cooling to obtain a precipitated solid; The micro-boiling state is when small bubbles appear on the surface of the liquid in the container, and the liquid at the heating point boils, but the liquid in the container as a whole does not boil, and is in a state before boiling; S5: The precipitated solid obtained after filtration is repeatedly washed with deionized water until its pH value is neutral, and then the solid is washed with anhydrous ethanol. The washed solid is dried to obtain a magnetic biochar adsorption material, and the magnetic biochar adsorption material is ground using a ball mill to obtain a magnetic biochar adsorbent for valuable metal recovery of lithium batteries.

2. The method for recovering valuable metals from lithium batteries using a magnetic biochar adsorbent according to claim 1, characterized in that: The wood selected in step S1 is one or more of paulownia, pine, willow, apple and peach.

3. The method for recovering valuable metals from lithium batteries using a magnetic biochar adsorbent according to claim 1, characterized in that: In step S1, an oven is used for drying, the temperature range of the oven is 60-80° C., and the drying time is 18-24 hours.

4. The method for recovering valuable metals from lithium batteries using a magnetic biochar adsorbent according to claim 1, characterized in that: In step S3, an oven is used for drying, the temperature range of the oven is 60-80° C., and the drying time is 6-8 hours.

5. The method for recovering valuable metals from lithium batteries using a magnetic biochar adsorbent according to claim 1, characterized in that: In step S4, the pH value of the solution is adjusted to a range of 10.0 to 11.0, and the pH value of the solution is adjusted by dropwise adding NH3·H2O into the solution.

6. The method for recovering valuable metals from lithium batteries using a magnetic biochar adsorbent according to claim 1, characterized in that: In step S5, an oven is used for drying, the temperature range of the oven is 60-80° C., and the drying time is 8-10 hours.

7. The method for recovering valuable metals from lithium batteries using a magnetic biochar adsorbent according to claim 1, characterized in that: In the step S5, the magnetic biochar adsorption material is ground using a ball mill, the grinding time is 0.5h~2h, and the particle size of the magnetic biochar adsorption material after grinding is 6.0~8.0μm.

Citation Information

Patent Citations

  • Magnetic chaff charcoal for removing lead and cadmium in water and preparation and application method thereof

    CN105797693A

  • Preparation method of adsorbent for removing phosphorus and heavy metal anions in water as well as application method

    CN105879834A

  • Preparation method of magnetic biochar adsorbing material for arsenic-cadmium combined pollution remediation

    CN106732350A

  • Preparation method of Fe3O4-based biochar soil passivating agent

    CN107824612A

  • Preparation method of magnetic mulberry stem biochar adsorbent

    CN109847695A